PENGARUH KONSUMSI REBUSAN DAUN SALAM SEBAGAI ANTIINFLAMASI TERHADAP NYERI SENDI OSTEOARTHRITIS : The Effect Of Consumption Bay Leaf Boiled As An Anti-Inflammatory Against Osteoarthritis Joint Pain - Anis Murniati; Eny Masruroh; Suciati; Yan Fuana (Jurnal Penelitian, 2024)
Osteoarthritis (OA)  is a joint disorder that affects all parts of the joint, especially cartilage, can have an impact on articular structural damage and loss of synovial joint function as well as causing chronic pain and requires treatment that has minimal side effects and cheap, so research on bay leaves has been carried out as an alternative solution. The research aims to determine the impact of consuming boiled bay leaves as an anti-inflammatory in reducing osteoarthritis pain. Quasi-experimental research design, use pretest posttest group design approach. Pain measurement uses the NRS scale. Samples were taken with a total sampling of 38 osteoarthritis sufferers in Wates Village. Data analysis using the Wilcoxon sign rank test with an interpretation error rate of α = 0.05. The result was that almost half of the respondents, 17 people (44.7%) experienced a decrease in the pain scale to mild pain after being given the consumption of bay leaf decoction with a P value = 0.000, meaning that there was an effect of consuming bay leaf decoction on reducing pain in osteoarthritis patients. Bay leaf bioled has effects on reducing pain in osteoarthritis sufferers because bay leaves contain tannins, flavonoids, alkaloids and essential oils, while flavonoids play an active role as anti-inflammatory by inhibiting transcription factors such as NF-κB. Inhibition of NFκB is part of the activity of flavonoids in inflammatory responses. This is similar to transcription factor and activation protein-1 (AP-1).   Keywords:  Anti-Inflammatory; Bay Leaf Boiled;  Osteoarthritis; Pain